New flexible and transparent solution-based germanium-sulfide polymeric materials - Salvi, Denise T. B. de [UNESP]; Job, Aldo E. [UNESP]; Ribeiro, Sidney J. L. [UNESP] (Soc Brasileira Quimica, 2015)
New flexible and transparent materials based on germanium sulfide were obtained using GeCl4 and 1,3-propanedithiol as precursors. These materials have transparency in the ultraviolet-visible (UV-Vis) spectral region (about 70%), thermal stability up to 200 degrees C and glass transition located at temperatures below 0 degrees C (-37 degrees C, -56 degrees C and -59 degrees C) as shown by differential scanning calorimetry (DSC) curves. Scanning electron microscopy (SEM) images showed that the polymer is homogeneous and presents formation of crystals in some regions of the surface. These polymers also exhibit Ge-S bonds in its structure, as can be observed through Fourier transform infrared (FTIR) (bands at 399, 401, 432 and 470 cm(-1)) and Raman (peaks at 361 and 430 cm(-1)) spectroscopies, and the diffraction patterns X-rays, which suggest the formation of a mixture of GeS2 and GeO2 phases (also confirmed through energy-dispersive X-ray analysis). The coupled thermogravimetric analysis / Fourier transform infrared (TG/FTIR) technique was used to investigate the degradation of the sample. Taken together, the results of these characterizations suggest optical applications, and usability at low temperatures.
Keywords: Germanium sulfide; Polymer; Solution-based; Transparent